Menumbuhkan Motivasi Belajar Siswa Pasca Pembelajaran Daring Akibat Pandemi COVID-19 - Yudhistari, Elsa; Purnomo, Heru (Trends in Applied Sciences, Social Science, and Education, 2023)
Learning motivation is a driving force for students to learn, ensuring the continuity of learning activities and providing direction for these activities to achieve a goal. Factors that can support the teaching and learning process are the teacher's ability to choose the right methods, strategies and learning models. Attractive learning strategies and models will not necessarily make students attractive to study offline after the COVID-19 pandemic. Motivation for students is needed to support success in the online learning process. Things that can be done by teachers in fostering student learning motivation include evaluating the tasks that have been done by students, giving prizes and praise for students who have successfully completed their assignments with maximum results, and punishments for students who have violated the rules.